(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Small scale industries play a vital role in the development of economy, mainly in developing countries. If population of India is taken into consideration it can be said that this sector has a wide scope in India. If small scale industrial sector is developed other economy related problems can be dissolved automatically. But these have to face so many problems while competing with other large scale industries. If these problems are solved or efforts are taken to foster these challenges this sector can prove itself as a developing engine.